2006
DOI: 10.1016/j.ydbio.2006.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the short stature homeobox gene Shox is restricted by proximal and distal signals in chick limb buds and affects the length of skeletal elements

Abstract: SHOX is a homeobox-containing gene, highly conserved among species as diverse as fish, chicken and humans. SHOX gene mutations have been shown to cause idiopathic short stature and skeletal malformations frequently observed in human patients with Turner, Leri-Weill and Langer syndromes. We cloned the chicken orthologue of SHOX, studied its expression pattern and compared this with expression of the highly related Shox2. Shox is expressed in central regions of early chick limb buds and proximal two thirds of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 37 publications
5
50
1
Order By: Relevance
“…For example, Shox misexpression throughout the developing chick limb bud results in an ossification delay in the coracoid of the scapula and the ischium of the hip. Furthermore, similar to the expression pattern of Shox2 in the developing mouse stylopod, expression of Shox is downregulated in chondrogenic condensations of the chick zeugopod (Tiecke et al, 2006). And finally, Shox overexpression in chick limb bud micromass cultures results in significantly depressed expression of the chondrocyte maturation genes Ihh (Tiecke et al, 2006) and Fgfr3 (Decker et al, 2011).…”
Section: Discussionmentioning
confidence: 63%
“…For example, Shox misexpression throughout the developing chick limb bud results in an ossification delay in the coracoid of the scapula and the ischium of the hip. Furthermore, similar to the expression pattern of Shox2 in the developing mouse stylopod, expression of Shox is downregulated in chondrogenic condensations of the chick zeugopod (Tiecke et al, 2006). And finally, Shox overexpression in chick limb bud micromass cultures results in significantly depressed expression of the chondrocyte maturation genes Ihh (Tiecke et al, 2006) and Fgfr3 (Decker et al, 2011).…”
Section: Discussionmentioning
confidence: 63%
“…It has indeed been previously shown that a human SHOX knock-in allele is able to compensate for the loss of mouse Shox2 in the developing forelimb (Liu et al 2011). Interestingly, the reported SHOX2 expression domains in chicks and humans are restricted to the stylopod (Clement-Jones et al 2000;Tiecke et al 2006), suggesting that the distally extended expression of mouse Shox2 may be a derived feature in rodents. And second, although the individual mutation of mouse Shox2 has little effect on the newborn zeugopod, its mutation in sensitized Hox backgrounds demonstrates its prominent function in this region.…”
Section: Discussionmentioning
confidence: 86%
“…In chick wing buds, Shox is expressed in an intermediate region where it overlaps Meis expression proximally. This expression pattern could be explained by the fact that Shox is inhibited by distal FGF and by proximal RA signals (Tiecke et al, 2006).…”
Section: Box 2 Experimental Evidence For the Morphogen Gradient Modementioning
confidence: 99%
“…In chick wing buds, Shox is expressed in an intermediate region where it overlaps Meis expression proximally. This expression pattern could be explained by the fact that Shox is inhibited by distal FGF and by proximal RA signals (Tiecke et al, 2006).In summary, significant progress has been made in identifying the molecules involved in PD limb patterning but this has not clarified whether this process is best explained in terms of the progress zone or early specification model. In fact, in the next section we describe how the dissection of FGF genetics in the mouse limb has led to an alternative model that, again, has classical roots.…”
mentioning
confidence: 99%